Optimalisasi Kotoran Kandang Menjadi Pupuk Organik Dengan Menggunakan Cacing Lumbricus Rubellus di Desa Kaliboja Pekalongan - Melliyana Melliyana; Miftakhul Ulum; Muhammad Bagus Alam; Muhammad Adin Setyawan (Universitas Teuku Umar, 2025)
Making organic fertilizer from manure waste using the role of worms can reduce pollution originating from manure waste. The more worms you cultivate, the greater the absorption of waste from the environment, so that environmental pollution resulting from piles of livestock manure can be reduced. Earthworms also have the ability to convert insoluble nutrients into soluble forms with the help of enzymes contained in the worm's digestion, so that they are absorbed more quickly by plants. The increasing development of animal husbandry provides opportunities for the development of organic fertilizer from manure on a wider scale. This not only has a positive effect on the environment but also opens up profitable business opportunities. The aim of this activity is to provide insight to breeders regarding the use of earthworms (Lumbricus rubellus) in converting manure waste into fertilizer, which can be used as fertilizer. organic in plant cultivation. The method used in this activity is to give a lecture about earthworms and fertilizer making, hold discussions and questions and answers, and practice fertilizer making activities. The impact obtained is an increase in farmers' knowledge regarding the role of earthworms in the fertilizer-making process or indirectly regarding the role of earthworms in animal husbandry.